A novel approach based on type-2 fuzzy sets to augment technology roadmaps - Barip, Semanur; Altun, Koray (GAZI UNIV, 2022)
Importance of RDI outputs is increasing day by day in the business world. Harmony of RDI activities and technology strategies is one of the important guarantees of sustainable success. At this stage, the first thing that comes to mind is the "technology roadmaps", which have been commonly used in order to direct RDI activities. Technology roadmaps are the tools linking technological developments and changes with other relevant layers (products, services, market, etc.), and thus they assist in decision making. To obtain a valid technology roadmap, its inter-element relationships need to be well-established. This study proposes an infographic for the relationships between technology roadmap elements. In this study, importance of the relationships and the relationship degree of element pairs are evaluated through the use of interval type-2 fuzzy systems (IT2FS). The infographic employing these evaluation results augments the technology roadmaps. In order to illustrate how the proposed process executes, a case of three-dimensional (3D) printing technologies is presented. Consequently, it is considered that these augmented technology roadmaps contribute to strategy planning and technology management, especially for large-scale cases.
Keywords: Technology roadmapping; relation analysis; fuzzy systems; 3D printing technologies